PENYESUAIAN POLA DASAR SISTEM DANCKAERTS PADA WANITA BERTUBUH GEMUK PENDEK - Hasanah, Nursanti; Yasnidawati, Yasnidawati; Nelmira, Weni (Journal of Home Economics and Tourism, 2015)
The aim of research is to describe the weakness basic pattern of Danckaerts system on a short fat woman, how to fix the weaknesses of Danckaerts basic pattern system on a short fat woman and the adjustment one short fat woman. Then the kind of research is applied research. The object research is a basic pattern of Danckaerts system which it tailored to the short fat woman. The rated by 5 panelists the result who is experts in the field of pattern. The instrument used a questionnaire with Likert scale. Techique of analysis use descriptive statistics in the form of the calculation formula porsentase and SPSS. The results showed that the basic pattern adjustment Danckaerts system on a short fat woman is classified into categories is in accordance with the achievement scores by 95% of respondents.Key words : Adjustment, basic pattern of Danckaerts system